Inclusiveness and Accessibility of University Facilities and Urban Spaces - De Leo, Daniela (Urbana, 2024)
This study examines the evolving relationship between European universities and their respective cities, exploring the multifaceted impact on economic and cultural development. The narrative encompasses the dual roles of universities as drivers of development and controversial entrepreneurial entities, drawing inspiration from concepts like the civic university.